IDENTIFIKASI PATOGEN PENYEBAB PENYAKIT TANAMAN SAWIT (Elaeis guineensis Jacq. ) Di DESA BERTAM KECAMATAN JAMBI LUAR KOTA - Yuza Defitri (Universitas Batanghari Jambi, 2015)
The research is about identification of pathogenic fungi in oil palm plant (Elaeis guineensis Jacq.) In Bertam Kecamatan Jambi Luar Kota and Agriculture Quarantine Laboartory Jambi has done for six months. The aim of this research is to identificated disease in oil palm plants (Elaeis guineensis Jacq.) that caused by fungi in Bertam Kecamatan Jambi Luar Kota. The research was conducted by observing the disease which in palm oil plants area, and identificated pathogenic fungi in laboratory in moist chamber and using microscop and also fungi identifications book.The result of this research is showed that the four pathogenic fungi which attack oil palm plants in Bertam Kecamatan Jambi Luar Kota namely: 1) Fusarium sp fungi rown Disease, 2) Curvularia fungi caused Leaf Disease, 3) Phytopthora sp fungi caused Leaf Rot disease and 4) Drechslera sp fungi which the cause of Drechslera leaft Disease.Key words : Identification, Patogenic fungi and Elaeis guineensis .